Assessment of mental health and quality of life status in health care professionals during COVID-19 in a tertiary care hospital in Jammu, India - Shafi, Basrat; Gupta, Rajiv K.; Kumari, Rashmi; Mir, Mehak T.; Hameed, Burhan; Gupta, Rishab; Kailu, Chaitanya; Hassan, Zahid Ul; Manhas, Sakshi (International Journal Of Community Medicine And Public Health, 2024)
Background: COVID-19 pandemic impacted all aspects of life in one way or the other may it be physical, mental or spiritual. The consequences following COVID-19 had a significant effect on quality of life (QOL) of all the people irrespective of caste, creed or religion. Methods: The present study was conducted among health care professionals (HCPs) in a tertiary care hospital in Jammu city of UT of Jammu and Kashmir. To measure the mental health, DASS-21 scale was used to ascertain the prevalence of depression, anxiety and stress. To assess the quality of life, the tool used was World Health Organisation quality of life scale (WHO QOL- BREF). Results: The data thus collected was analysed and chi square test was used as a test of significance. A total of 250 health care professionals were assessed and prevalence of depression, anxiety and stress was found to be 51.2%, 18% and 45.2% respectively. Gender was significantly associated with anxiety (p<0.05) while education levels had a statistically significant associated with anxiety and stress (p<0.05). All domains of QOL were found to be on higher side among male health care professionals and respondents living in urban areas. There was a statistically significant association between QOL and level of education (p<0.05). Conclusions: The study has demonstrated that COVID-19 was negatively related to health care professionals’ mental health and QOL. In this context authors recommend targeted interventions to ameliorate both mental health as well as QOL.